Ways to increase the sustainability of the agricultural sector of the economy - Sharyi, G.; Nesterenko, S.; Shchepak, V. (Land Management, Cadastre and Land Monitoring, 2021)
Abstract. The factors causing destruction of natural complexes, degradation of agricultural lands were considered. It was revealed that the crisis phenomena of state institutions also influenced the low resistance of agricultural production to negative impacts of a natural and climatic nature. The necessity of raising the urgent problem of drought, which affects the decrease in yield, and, consequently, the deterioration of the natural conditions of the economy, was proved. This requires a change in the agricultural technology system towards the development of a reclamation complex for the irrigation of agricultural lands, especially on lands of intensive agriculture, in particular, beet growing, vegetable growing, fodder production and the formation of a more drought-resistant farming system. It was noted that the neoliberal regulatory policy of the state and the liberalization of agrarian relations stopped the development of intensive reclaimed agriculture. It was revealed that over the past 30 years, land with reclamation systems fell into the private property of individuals. Lack of responsibility for the proper use of irrigation systems has led to the rupture of technological integrity, to the destruction of their functional properties. There is a need to form a system for organizing the efficient and rational use of agricultural land in production, which will allow us to study the features of the interaction of the components of the system and form ways to ensure a balance between the efficiency (profitability) of production and rational continuous use of agricultural land. On the basis of modeling, the factors of influence on the organization of the effective use of agricultural lands were determined. A graph-model of the system of organizing the efficient and rational use of agricultural lands was formed A structural-logical model of overcoming drought on agricultural lands was proposed. As a result of the studies, it was concluded that the impact of drought can be overcome by ensuring in Ukraine a full-fledged turnover of agricultural land and effective state mechanisms of regulatory economic policy in agricultural land use. Keywords: agricultural land, drought, land reclamation, model, system, rational use of land, sustainability of agricultural production.